Analisa Faktor-Faktor Yang Berkontribusi Terhadap Kenaikan Berat Badan Pada Akseptor KB Suntik 3 Bulan Di Desa Kesilir, Kecamatan Wuluhan Jember - Evi Nurhidayah; Rifzul Maulina (Journal of Innovative and Creativity, 2025)
Introduction: The family planning program can reduce maternal mortality for mothers. The side effects of using 3-month injectable contraceptives are changes in the hormone progesterone or weight gain. The factors that influence weight gain for acceptors who use 3-month injectable birth control are length of use, parity, and physical activity. The purpose of this study is to determine the relationship of factors that contribute to weight gain. Methods: This study used a cross sectional research design. Data collection was carried out using the observation method with a total sample of 20 respondents. Data analysis technique using Chi Square test with p value <0.05. Results: The results of the study using the chi square test showed that the p value of parity was 0.04, the p value of length of use of birth control was 0.4, and the p value of physical activity was 0.01. Conclusion: Parity and physical activity have a significant relationship with the increase in body weight of acceptors who use 3-month injectable family